2018
DOI: 10.1136/bjophthalmol-2017-311453
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with diabetic anterior uveitis

Abstract: We characterised new-onset anterior uveitis in 18 patients in association with poorly controlled or undiagnosed diabetes mellitus. The uveitis was managed in all cases with local corticosteroid therapy in addition to proper diabetes systemic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
2
5
0
1
Order By: Relevance
“…Common causes of uveitis were idiopathic uveitis, traumatic uveitis, ankylosing spondylitis with uveitis, uveitis after intraocular lens surgery, rheumatoid arthritis with uveitis, Vogt–Koyanagi–Harada syndrome, and tuberculosis combined with uveitis. In this study, 29 cases were mainly idiopathic uveitis, accounting for 55.77%, followed by 7 cases (13.46%) of traumatic uveitis and 4 cases of ankylosing spondylitis combined with grapevine meningitis (7.69%), which was consistent with previous reports at home and abroad [ 13 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Common causes of uveitis were idiopathic uveitis, traumatic uveitis, ankylosing spondylitis with uveitis, uveitis after intraocular lens surgery, rheumatoid arthritis with uveitis, Vogt–Koyanagi–Harada syndrome, and tuberculosis combined with uveitis. In this study, 29 cases were mainly idiopathic uveitis, accounting for 55.77%, followed by 7 cases (13.46%) of traumatic uveitis and 4 cases of ankylosing spondylitis combined with grapevine meningitis (7.69%), which was consistent with previous reports at home and abroad [ 13 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that the proportion of male uveitis patients was significantly higher than that of females (3.33 : 1), which was consistent with the domestic research results of Zhang et al [ 9 ] and Li et al [ 10 ], indicating that uveitis was more common in our country male, but some foreign reports [ 11 , 12 ] show “female than male,” the reason might be that there were regional differences in the incidence of the disease. In this study, the age of onset was mostly 21–40 years, suggesting that uveitis occurs frequently in young adults, which was consistent with reports at home and abroad [ 13 15 ]. Common causes of uveitis were idiopathic uveitis, traumatic uveitis, ankylosing spondylitis with uveitis, uveitis after intraocular lens surgery, rheumatoid arthritis with uveitis, Vogt–Koyanagi–Harada syndrome, and tuberculosis combined with uveitis.…”
Section: Discussionsupporting
confidence: 91%
“…It is not certain whether our patients with medical history of DM accidentally suffered from idiopathic uveitis or if DM was the direct cause of uveitis Glycaemic improvements may prevent recurrence [44]. Association between poorly controlled DM and anterior uveitis was seen from report Japan [45].…”
Section: Discussionmentioning
confidence: 99%
“…Statine, ACE-Hemmer, Diabetes mellitus (DM) und Rauchen zeigten keinen Einfluss auf die Remission, auch wenn andere Studien einen Einfluss von DM auf das Auftreten von Uveitiden [2] und bei Rauchern eine höhere Rezidivneigung gezeigt hatten [3].…”
Section: Transfer In Die Praxis Von Dr Vita Dingerkus Und Prof Dr unclassified